2006
DOI: 10.1177/0893318906291980
|View full text |Cite
|
Sign up to set email alerts
|

Nightmares, Demons, and Slaves

Abstract: Although considerable research has linked workplace bullying with psychosocial and physical costs, the stories and conceptualizations of mistreatment by those targeted are largely untold. This study uses metaphor analysis to articulate and explore the emotional pain of workplace bullying and, in doing so, helps to translate its devastation and encourage change. Based on qualitative data gathered from focus groups, narrative interviews, and target drawings, the analysis describes how bullying can feel like a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(89 citation statements)
references
References 66 publications
4
78
0
7
Order By: Relevance
“…Separately, these resources each partially mediated the relationship, but taken together they provided full mediation. This replicates previous findings on social resources (Djurkovic et al, 2008;Leather et al, 1998;Schat & Kelloway, 2003;Soares et al, 2000;Tracy et al, 2006), and also provides some initial evidence of an important role for psychological capital in regard to bullying at work. The individual predictions that (i) psychological capital would be related negatively to ill-being and positively to wellbeing, and (ii) the experience of bullying would be related positively to ill-being and negatively to well-being, were supported by the findings from the correlation analysis as well as from the model fit.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Separately, these resources each partially mediated the relationship, but taken together they provided full mediation. This replicates previous findings on social resources (Djurkovic et al, 2008;Leather et al, 1998;Schat & Kelloway, 2003;Soares et al, 2000;Tracy et al, 2006), and also provides some initial evidence of an important role for psychological capital in regard to bullying at work. The individual predictions that (i) psychological capital would be related negatively to ill-being and positively to wellbeing, and (ii) the experience of bullying would be related positively to ill-being and negatively to well-being, were supported by the findings from the correlation analysis as well as from the model fit.…”
Section: Discussionsupporting
confidence: 87%
“…Researchers have found that co-worker support is important in reducing the negative impact of bullying (Djurkovic, McCormack, & Casimir, 2008;Leather, Lawrence, Beale, Cox, & Dickson, 1998;Schat & Kelloway, 2003;Soares, Lawoko, & Nolan, 2000;Tracy, Lutgen-Sandvik, & Alberts, 2006) and that victims of bullying tend to report less support from co-workers (Hansen et al, 2006). In the literature on stress and coping, social support has been unanimously demonstrated as a key variable in both mediating and moderating stress (Cassidy, 2011).…”
Section: Please Scroll Down For Articlementioning
confidence: 96%
“…A diversity leadership challenge is the paucity of leadership practices that respond appropriately to diversity problems (Aguirre, 2008). Another challenge is workplace bullying (Lutgen-Sandrik & Alberts, 2006), which can occur because of gender or race (Lutgen-Sandrik & Alberts, 2006). Because competition, power struggles, envy and prejudice characterise diverse workplaces, they can trigger bullying (Heames & Harvey, 2006).…”
Section: Diversitymentioning
confidence: 98%
“…Bullying causes great emotional pain to its victims (Lutgen-Sandvik, 2008;Tracy et al, 2006) but also has financial costs to the organizations concerned. As an example of this, according to one UK report, bullying costs the UK economy £13.75 billion per year (Anonymous, 2008).…”
mentioning
confidence: 99%